Dynamic and static nature of activated interactions in transition states as elucidated by quantum theory of atoms‐in‐molecules dual functional analysis: A case of ligand exchange at the N of sulfonylimino‐λ3‐bromanes. Issue 4 (5th November 2019) - Nakanishi, Waro; Hayashi, Satoko; Nishide, Taro; Otsuki, Shota
Abstract: A method to elucidate the dynamic and static natures of the activated interactions in transition states (TSs) is proposed using quantum theory of atoms‐in‐molecules (QTAIM) dual functional analysis (QTAIM‐DFA). The natures are determined for the ligand exchange at the N of sulfonylimino‐λ 3 ‐bromanes, RBr‐*‐N(SO2 CF3 )‐*‐X′R′ (R, R′ = Me or Ph, X′ = Br′ or I′). Asterisks (*) emphasize the presence of bond critical points within the interactions in question. While data from the optimized structures of TSs correspond to the static nature, those from the perturbed and optimized structures represent the dynamic nature. The nature of the interactions in Br‐*‐N‐*‐X′ calculated with QTAIM‐DFA, using the perturbed structures generated using the normal coordinates for the imaginary frequencies (NIV), was very similar to that in trigonal bipyramidal adduct formation through charge transfer. The results with NIV were precisely the same as those obtained based on intrinsic reaction coordinate (IRC). The high applicability of QTAIM‐DFA is demonstrated when analyzing the activated interactions in TSs. Abstract : The behavior of interactions in transition states is elucidated for RBr‐*‐N(SO2 CF3 )‐*‐X′R′ (R, R′ = Me or Ph; X′ = Br or I) using quantum theory of atoms‐in‐molecules (QTAIM) dual functional analysis by applying the perturbed structures generated with NIV, the normal coordinates for the imaginary frequencies. The interactions are predicted to have a CT‐TBP nature (TBP adducts formed through CT).